A microfludic transistor-based platform concept facilitating on-chip flow control - Frank, Philipp; Graefe, David; Haefner, Sebastian; Elstner, Martin; Appelhans, Dietmar; Voit, Brigitte; Richter, Andreas (20th International Conference on Miniaturized Systems for Chemistry and Life Sciences, MicroTAS 2016, 2016)
We demonstrate a microfluidic platform concept, which utilizes the volume phase transition of stimuli-responsive hydrogels to actively switch between fluid streams on-chip in a discrete operating manner. The central element is a chemo-fluidic transistor, which couples the chemical content of a fluid with the fluidic domain and therefore facilitates direct feedback. The concept relies on wellestablished electronic circuit paradigms and the chemo-fluidic transistor, which is capable to autonomously make switching decisions exclusively depending on a chemical input. In this study we developed basic logic gates, sequential modules and a chemo-fluidic oscillator.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Chemo-fluidic transistor; Hydrogel; Integrated circuits; Microfluidic